(untitled) (International relations and international law Journal, 2016)
This paper focuses on analysis of legal instruments for the implementation of international cooperation of the Republic of Kazakhstan. The article also considers the problem of global climate change related to the expected warming caused by greenhouse gas emissions. Considering and analyzing the views of well-known politicians, the author stresses the need to establish governmental body responsible for environmental protection in Kazakhstan. Its functions are a list of strategically important natural objects to be protected against acts of sabotage and emergencies and to ensure their protection; determine the international conventions, treaties and decide – what documents for Kazakhstan is necessary to join to.